MENINGKATKAN KEMAMPUAN MENGENAL WARNA DENGAN METODE EKSPERIMEN BERMAIN WARNA PADA ANAK KELOMPOK B TK KHADIJAH 202 KARANGSARI SEMPU - Nur Asiyah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
The ability to know the color is very important in a child's life. Process to improve children's ability to recognize colors can be improved through a learning process that involves children in finding something of his own experience in learning. It can enhance the formation of children's cognitive structure so that the child is able to know, discover and understand conceptually color. The purpose of this study to describe how to improve children's ability to recognize colors through the experimental method in group B TK Khadijah 202 Karangsari Sempu. The results showed the experimental method can improve the ability to know the color of the child with the percentage 62.50% achieve mastery class.